The Imperium of the Colonial Tongue? Evidence on Language Policy Preferences in Zambia. (16th March 2022) - Ramachandran, Rajesh; Rauh, Christopher
Abstract: Sub-Saharan Africa stands out as a part of the world that primarily uses, as its official languages, former colonial languages that are neither spoken at home nor in the community. In this paper, we elicit preferences for colonial versus local languages and analyse the role of perceived costs and returns to different languages. In order to do so, we elicit beliefs about the effects of hypothetical changes to Zambia's language policy on schooling outcomes, income and social cohesion. Our results show overwhelming support for the use of the colonial language to act as official. Looking at the determinants, we find that fears of being disadvantaged by the installation of another group's language, high perceived costs of learning in another group's language and lack of association between retaining the elite language and socioeconomic inequality as crucial factors in affecting preferences over language policies.